An Increased Anticholinergic Drug Burden Index Score Negatively Affect Nutritional Status in Older Patients Without Dementia - Ates Bulut, Esra; Erken, Neziha; Kaya, Derya; Dost, Fatma Sena; Isik, Ahmet Turan (Frontiers in Nutrition, 2022)
Introduction/Aim: Anticholinergic drugs, which have severe central and peripheric side effects, are frequently prescribed to older adults. Increased anticholinergic drug burden is associated with poor physical and cognitive functions. On the other side, the impact of anticholinergics on nutritional status is not elaborated in the literature. Therefore, this study was aimed to investigate the effect of the anticholinergic burden on nutrition. Materials and Methods: Patients who underwent comprehensive geriatric assessment(CGA) six months apart were included in the study. Patients diagnosed with dementia were excluded because of the difference in the course of cognition, physical performance and nutrition. Nutritional status and global cognition were evaluated using Mini Nutritional Assessment-short form(MNA-SF), Mini-Mental State Examination(MMSE). Anticholinergic drug burden was assessed with the Drug Burden Index(DBI), enabling a precise dose-related cumulative exposure. Patients were divided into three groups according to DBI score: 0, no DBI exposure; 0 – 1, low risk; and ≥ 1, high risk. Regression analysis was performed to show the relationship between the difference in CGA parameters and the change in DBI score at the sixth month. Results: A total of 423 patients were included in the study. Participants’ mean age was 79.407.50, and 68.6% were female. The DBI 0 score group has better MMSE and MNA-SF scores and a lower rate of falls, polypharmacy, malnutrition, and risk of malnutrition in the baseline. Having malnutrition or risk of malnutrition is 2.21 times higher for every one-unit increase in DBI score. Additionally, during the six-month follow-up, increased DBI score was associated with decreased MNA-SF and MMSE score, albumin. Conclusions: The harmful effects of anticholinergics may be prevented because anticholinergic activity is a potentially reversible factor. Therefore, reducing exposure to drugs with anticholinergic activity has particular importance in geriatric practice.